EFFECT OF EFFLEURAGE TECHNIQUES TO INTENSITY PAIN ON DELIVERING BABY AT 1st PERIOD ACTIVE PHASE Of MOTHERS DELIVERING BABY IN BPM Hj.NINIK ARTINGSIH.,SST.M.Kes BLOOTO DISTRICT MOJOKERTO - ariu dewi yanti; Rina mardiyana mardiyana (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
The pain on delivering baby was experienced by most women, this pain is unique and different for every individual. Non-pharmacological pain control becomes cheaper, simple, and effective and without adverse effects, one of which is the technique effleurage. Effleurage of the abdomen is one of the non-pharmacological methods which are usually used in the Lamaze method to reduce pain in normal labor. This research aimed to determine the effect of effleurage technique on active phase of the first stage of labor pain intensity on maternal in private midwife Hj.Ninik Artiningsih.,SST.M.Kes Blooto District Mojokerto Regency. Research design was pre experimental type one group pre-test post test design. Its population were all women giving birth in BPM Hj.Ninik Artiningsih.,SST.M.Kes, SST Blooto distric Mojokerto Regency amount 17 people. The sampling technique used consecutive sampling to obtain 15 samples. Data analysis used was Wilcoxon test with P value <0.05. It means that there was effect of effleurage technique on active phase of the first stage of labor pain intensity on maternal in private midwife Hj.Ninik Artiningsih.,SST.M.Kes Blooto District Mojokerto Regency. Gently cares the abdomen effected in pain that transmitted will be inhibited, it effected in the cerebral cortex does not receive the response message so that the pain decreased pain